Biphasic epoxy-ionic liquid structural electrolytes: minimising feature size through cure cycle and multifunctional block-copolymer addition. Issue 3 (9th September 2021) - Wendong, Quan; Dent, John; Arrighi, Valeria; Cavalcanti, Leide; Shaffer, Milo S P; Shirshova, Natasha
Abstract: Structural electrolytes provide mechanical properties approaching structural resin combined with a high degree of ionic conductivity. Here, structural electrolytes based on bisphenol A diglycidyl ether and the ionic liquid 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl) imide (EMIM-TFSI) were synthesised through reaction induced phase separation (RIPS) using isophorone diamine (iPDA) as a curing agent. The microstructure and properties of the resulting materials were controlled through both the initial formulations and the curing temperature. Curing at room temperature generated a bi-continuous structure and improved both mechanical performance and ionic conductivity of the resulting structural electrolytes. The balance between properties can be systematically adjusted; for example, a promising Young's modulus of 800 MPa was obtained simultaneously with an ionic conductivity of 0.28 mS cm −1, for a formulation containing 35 vol% EMIM-TFSI. The lengthscale of the structural features was reduced by an order of magnitude by introducing multifunctional block-copolymers (MF-bcP) based on glycidyl methacrylate (GMA) and quaternised (2-dimethylamino)ethyl methacrylate (DMAEMA). Small angle neutron scattering (SANS), obtained during curing, identified at least two structural phases of different length scale, for the formulations containing MF-bcP, in agreement with microstructures observed using scanning electron microscopy. Such structural electrolytes may be required when using structural electrodes that also have finer characteristic lengthscales. The addition of the MF-bcP to formulations containing 35 vol% EMIM-TFSI produced structural electrolytes with a Young's modulus of 530 MPa and an ionic conductivity of 0.64 mS cm −1 .